Herbal synergy enhances growth performance, antioxidant status, immunity, and lymphoid tissue architecture in pigeons - Rasha I. M. Hassan; Hala Y. Amer; Walaa M. S. Gomaa; Ramadan D. EL-Shoukary; Abeer M. Hassan; Asmaa A. Rayan; Fatma El-Zahraa A. Mustafa (Scientific Reports, 2025)
Abstract This study evaluated the effects of a herbal mixture (HM) composed of black seeds, dill, sage, and coriander on pigeon squabs and their parents. Using a randomized design, 54 squabs were divided into three groups. All groups were fed a basal diet, and HM was added to groups 2 and 3 at 1% and 2%, respectively. To receive crop milk, squabs were caged with their parents. Squab performance and the self-maintenance behaviors (sleeping and preening) of their parents were positively affected by HM supplementation ( P = 0.001). Blood metabolites, including cholesterol, triglycerides, and low-density lipoprotein cholesterol (LDL-C), were significantly decreased ( P = 0.001). Antioxidation biomarkers glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) were positively stimulated. The meat’s chemical composition, including fat, protein, amino acids, and moisture, was influenced by HM ( P = 0.004). Histomorphometrical investigation of the bursa and spleen showed the significant effects of HM on the follicle area, medulla, white pulp area, and their S100-positive cells. Overall, adding HM, especially at a 1% concentration, was more cost-effective and improved pigeon parents’ behavior, squabs’ performance, immunity, antioxidant status, meat quality, and bursal and spleen histology and immunohistochemistry.